1994
DOI: 10.1093/ajcn/59.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Reduced nutritional status in an elderly population (> 70 y) is probable before disease and possibly contributes to the development of disease

Abstract: In this prospective study of elderly people, nutritional status (body mass index, triceps skinfold thickness, arm-muscle circumference, and serum albumin) was assessed in a group of recently hospitalized (< 48 h) patients (n = 311), and compared with a home-living group (n = 106). Undernutrition was present in 52.9% of males and 60.6% of females by the time of admission to the hospital. Further, 65% of the males and 69% of the females had an insufficient energy intake the month before hospitalization [males < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
2
9

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(118 citation statements)
references
References 30 publications
3
104
2
9
Order By: Relevance
“…Protein-energy undernutrition in older persons will result in immune dysfunction and an increased risk of infections (Morley, 1995). Another consequence of undernutrition is an increased risk of hospitalization (Mowé et al 1994). Correspondingly, follow-up data showed an increase in the hospitalization rate among the twenty subjects judged to be at nutritional risk in 1988 by means of the MNA.…”
Section: Discussionmentioning
confidence: 96%
“…Protein-energy undernutrition in older persons will result in immune dysfunction and an increased risk of infections (Morley, 1995). Another consequence of undernutrition is an increased risk of hospitalization (Mowé et al 1994). Correspondingly, follow-up data showed an increase in the hospitalization rate among the twenty subjects judged to be at nutritional risk in 1988 by means of the MNA.…”
Section: Discussionmentioning
confidence: 96%
“…Biochemical mechanisms of this phenomenon will be discussed in the next paragraph. It has been found, however, that 65 % of elderly men and 69 % of elderly women had an insufficient energy intake already in the month before hospitalization (Mowe et al 1994). The authors have found that this inadequate food intake may partly contribute to a reduced nutritional status and increase the occurrence of hospitalization in a vulnerable group of elderly people.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…loss of appetite, decreased taste and odour perception) or a combination of some factors (Morley, 1996;Morley & Silver, 1988;Roberts et al, 1994;. This so-called`anorexia of aging' may have serious consequences, such as severe weight loss after the age of 70 y that is associated with nutrition-related diseases (Rajala et al, 1990;Losonczy et al, 1995;Mowe  et al, 1994).…”
Section: Introductionmentioning
confidence: 99%